2017
DOI: 10.1016/j.ijpddr.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Reduced efficacy of albendazole against Ascaris lumbricoides in Rwandan schoolchildren

Abstract: Control of human soil-transmitted helminths (STHs) relies on preventive chemotherapy of schoolchildren applying the benzimidazoles (BZ) albendazole or mebendazole. Anthelmintic resistance (AR) is a common problem in nematodes of veterinary importance but for human STHs, information on drug efficacy is limited and routine monitoring is rarely implemented. Herein, the efficacy of single dose albendazole (400 mg) was evaluated in 12 schools in the Huye district of Rwanda where Ascaris is the predominant STH. Asca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(130 citation statements)
references
References 53 publications
5
122
2
1
Order By: Relevance
“…in Timor-Leste Susana. Exceeding our results for A. lumricoides Krücken et al, [28] reported a pre-ADZ treatment prevalence of 33.3% for Ascaris in Rwandan schoolchildren, and Augusto et al, [29] detected 65.8% rate in children and young adults in Mozambique.…”
Section: Discussionsupporting
confidence: 49%
“…in Timor-Leste Susana. Exceeding our results for A. lumricoides Krücken et al, [28] reported a pre-ADZ treatment prevalence of 33.3% for Ascaris in Rwandan schoolchildren, and Augusto et al, [29] detected 65.8% rate in children and young adults in Mozambique.…”
Section: Discussionsupporting
confidence: 49%
“…Anthelmintic resistance is already a significant problem in veterinary medicine [7], and currently is suspected to be developing in nematodes that infect humans [8]. The economic impact of AR in farm animals is caused by direct production losses such as losses due to clinical and subclinical disease despite treatment, costs for testing of anthelmintic efficacy and the use of new, more expensive classes of anthelmintics [9].…”
Section: Introductionmentioning
confidence: 99%
“…Resistance against one particular anthelmintic drug is typically accompanied by resistance against other members belonging to the same class (i.e., side-resistance, as opposed to cross-and multidrug-resistance, which refers to resistance against two or multiple drugs belonging to different anthelmintic drug classes) [31]. Anthelmintic resistance has been claimed to occur occasionally also in human intestinal nematodes [35,36], but this is controversial [10,37,38]. It may only be a matter of time before this phenomenon becomes common in helminths of humans [23,39].…”
Section: Heterocyclic Compoundsmentioning
confidence: 99%
“…The authors concluded that plants from the Leguminosae family may offer an alternative source for the control of gastrointestinal nematodes of small ruminants. (5,6,7,17,19,26,27,28,31,32,33,34,36), saponin (4,25), terpenoids (12,13,15,16,18,37), alkaloids (1,2,3,8,9), coumaric acid (14,29,30), miscellaneous (10,11,20,21,22,24).…”
Section: Natural Products Active Against Intestinal Parasitic Nematodesmentioning
confidence: 99%